Mass production studies in solid substrates with the entomopathogenic fungus, Purpureocillium lilacinum - Barra, Paula Sabina (2018)
The objective of this study was to evaluate several substrates to determine the optimal condition of entomopathogenic mass production with the purpose of developing a mycoinsecticide to be used for an integrated pest management. Conidial quality and yield for two isolates of Purpureocillium lilacinum were determined. For quality parameters assessment, germination and purity percentage and viability of conidia were determined. For the production parameters, the conidial yield was calculated. The main results obtained show the type of substrate that had the greatest effect on the viability, germination and yield of conidia of P. lilacinum. The substrate that presented the highest production of conidia per gram was rice, showing 2.1×109 for isolate JQ926212 and 1.6×109 for JQ926223. In the particulate substrates, the percentage purity was about 99%, while in powder substrate, the percentage purity was low with values ranging from 23 to 75%. The highest percentage of moisture content was about 40% for rice and wheat, while for maize meal and vermiculite the percentage was close to 20%. In conclusion, P. lilacinum can be mass multiplied in rice grains and vermiculite.